(untitled) (Journal of Economic Additions, 2025)
This study investigates two group of taxpayers’ resistance to tax-platform change. The research also tries to broaden the UTAUT model by incorporating two additional constructs: privacy and risk in analyzing the motivation for taxpayer to utilize e-receipts’ platform. A survey was distributed online. During a 34-day period, 287 responses were obtained. We found more suitable model for describing the antecedents of intention use than the original one, when applied to the taxable person of VAT purposes’ user. In addition to UTAUT model, we found perceive risk is significantly as mediating of perceived privacy and usage intention. The findings should assist the tax authority in encouraging taxpayers to use e-receipts’ platform. Jel Classification Codes: M12, M14, D83, L86